Risk of stillbirth among Zambian women with a prior cesarean delivery. Issue 3 (15th October 2018) - Castillo, Marcela C.; Vwalika, Bellington; Stoner, Marie C.D.; Chi, Benjamin H.; Stringer, Jeffrey S.A.; Kasaro, Margaret; Kumwenda, Andrew; Stringer, Elizabeth M.
Abstract: Objective: Cesarean delivery (CD) may be associated with stillbirth in future pregnancies. We investigated prior CD as a risk factor for stillbirth in Lusaka, Zambia. Methods: We conducted a retrospective cohort analysis of women with only one prior pregnancy who delivered between February 1, 2006, and May 31, 2013. We analysed data from the Zambia Electronic Perinatal System. Maternal and infant characteristics were analyzed for association with stillbirth using Pearson's χ 2 test or the Wilcoxon rank‐sum test. We calculated risk ratios for the relationship between stillbirth (antepartum vs intrapartum) and prior CD, with a log Poisson model to adjust for confounding. Results: Of 57 320 women in our cohort, 1933 (3.4%) reported a prior CD. There were 1012 (1.8%) stillbirths in the no prior CD group and 81 (4.2%) in the prior CD group ( P <0.001). In multivariate models adjusting for stillbirth risk factors, prior CD was associated with antepartum (adjusted risk ratio 1.56, 95% confidence interval 1.08–2.24) and intrapartum (adjusted risk ratio 3.26, 95% confidence interval 2.40–4.42) stillbirth compared with no prior CD. The difference between groups was most apparent at 36–37 weeks' gestation (log‐rank P <0.001). Conclusion: Prior CD was associated with increased risk of stillbirth. Improved monitoring during labor and safe methods for induction are urgently needed in low‐resource settings. Abstract : Prior cesarean delivery is a risk factor for antepartum and intrapartum stillbirth in Lusaka, Zambia.